2019
DOI: 10.1021/acs.nanolett.9b02324
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Amyloid Materials Integrating Robustness and Genetically Programmable Functionality

Abstract: The precise manipulation, localization, and assembly of biological and bioinspired molecules into organized structures have greatly promoted material science and bionanotechnology. Further technological innovation calls for new patternable soft materials with the long-sought qualities of environmental tolerance and functional flexibility. Here, we report a patterned amyloid material (PAM) platform for producing hierarchically ordered structures that integrate these material attributes. This platform, combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…For instance, a functional amyloid protein CsgA was used to develop a material platform for producing hierarchically ordered fibrous mictrostructures. [ 44 ] CsgA is a protein expressed in Escherichia coli , which naturally self‐assembles into functional amyloid fibers forming an extracellular matrix encapsulating the bacteria within a biofilm. [ 45 ] Using a combination of soft lithography with CsgA monomer inks, the protein could be transferred onto surfaces.…”
Section: Structuring Of Protein‐based Materials For Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a functional amyloid protein CsgA was used to develop a material platform for producing hierarchically ordered fibrous mictrostructures. [ 44 ] CsgA is a protein expressed in Escherichia coli , which naturally self‐assembles into functional amyloid fibers forming an extracellular matrix encapsulating the bacteria within a biofilm. [ 45 ] Using a combination of soft lithography with CsgA monomer inks, the protein could be transferred onto surfaces.…”
Section: Structuring Of Protein‐based Materials For Applicationsmentioning
confidence: 99%
“…The robustness of the CsgA self‐assembly enabled also the fusion with tags such as a polyhistidine‐tag fused to the C‐terminus of CsgA for binding of inorganic nanoparticles, or CsgA‐CBD with a fused chitin‐binding domain (CBD) acting as a linker between chitin and CsgA nanofibers and enabling self‐supporting patterned porous sheets. [ 44 ]…”
Section: Structuring Of Protein‐based Materials For Applicationsmentioning
confidence: 99%
“…While it was already shown thirty years ago that the presence of interfaces can also stimulate protein and peptide aggregation [ 31 ], surface- and interface-related effects have only recently become a focus of attention [ 32 , 33 , 34 ]. This recent development was mostly motivated by the potential of nanoparticle-based strategies to mitigate amyloid-associated diseases [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], as well as by promising applications of amyloid fibrils in materials’ synthesis [ 44 , 45 , 46 , 47 , 48 ]. Nevertheless, the manifold effects of the physicochemical surface properties on amyloid aggregation and the involved molecular mechanisms are far from understood [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…29 Therefore, their removal from drinking water is absolutely necessary, but due to their dimensions smaller than 1 nm, it is difficult to remove them in current water treatment processes, even via ultraltration, microltration and nanoltration. 30 Earlier studies revealed that amyloid hybrid membranes (AHM) may be able to remove bacteria by a size-exclusion mechanism, [31][32][33][34] but we did not investigate this effect systematically, nor considered whether genetic material from biological contamination could be removed from water by the same membranes. This paper focuses on the removal efficiency of the amyloid hybrid membranes for both bacteria and genetic material by the systematic investigation.…”
Section: Introductionmentioning
confidence: 99%